Cancer Stem Cells and Radioresistance: Rho/ROCK Pathway Plea Attention. (15th August 2016) - Pranatharthi, Annapurna; Ross, Cecil; Srivastava, Sweta
Abstract : Radiation is the most potent mode of cancer therapy; however, resistance to radiation therapy results in tumor relapse and subsequent fatality. The cancer stem cell (CSC), which has better DNA repair capability, has been shown to contribute to tumor resistance and is an important target for treatment. Signaling molecules such as Notch, Wnt, and DNA repair pathways regulate molecular mechanisms in CSCs; however, none of them have been translated into therapeutic targets. The RhoGTPases and their effector ROCK-signaling pathway, though important for tumor progression, have not been well studied in the context of radioresistance. There are reports that implicate RhoA in radioresistance. ROCK2 has also been shown to interact with BRCA2 in the regulation of cell division. Incidentally, statins (drug for cardiovascular ailment) are functional inhibitors of RhoGTPases. Studies suggest that patients on statins have a better prognosis in cancers. Data from our lab suggest that ROCK signaling regulates radioresistance in cervical cancer cells. Collectively, these findings suggest that Rho/ROCK signaling may be important for radiation resistance. In this review, we enumerate the role of Rho/ROCK signaling in stemness and radioresistance and highlight the need to explore these molecules for a better understanding of radioresistance and development of therapeutics.